Plasma ddPCR for the detection of amplification in advanced NSCLC patients: a comparative real-world study - Jun-Wei Su; Cheng-Di Weng; Xiao-Cheng Lin; Mei-Mei Fang; Xiao Xiao; Yi-Chen Zhang; Xu-Chao Zhang; Jian Su; Chong-Rui Xu; Hong-Hong Yan; Hua-Jun Chen; Yi-Long Wu; et al. (Therapeutic Advances in Medical Oncology, 2024)
Background: Mesenchymal–epithelial transition ( MET ) amplification is a crucial oncogenic driver and a resistance mechanism to epidermal growth factor receptor tyrosine kinase inhibitors (TKIs) of non-small-cell lung cancer (NSCLC). Fluorescence in situ hybridization (FISH) is the gold standard for MET amplification detection. However, it is inapplicable when tissue samples are unavailable. Objective: This study assessed the performance of plasma droplet digital polymerase chain reaction (ddPCR) in MET amplification detection in NSCLC patients. Design and methods: A total of 87 NSCLC patients were enrolled, and 94 paired tissue and plasma samples were analyzed for the concordance between FISH and plasma ddPCR/tissue next-generation sequencing (NGS) in detecting MET amplification. In addition, the efficacy of patients with MET amplification using different detection methods who were treated with MET-TKIs was evaluated. Results: Plasma ddPCR showed substantial concordance with FISH (74.1% sensitivity, 92.5% specificity, and 87.2% accuracy with a kappa value of 0.68) and outperformed tissue NGS (kappa value of 0.64) in MET amplification detection. Combined plasma ddPCR and tissue NGS showed substantial concordance with FISH (92.3% sensitivity, 89.2% specificity, and an accuracy of 90.1% with a kappa value of 0.77). The efficacy is comparable in these NSCLC patients with MET amplification detected by FISH and plasma ddPCR who were treated with MET-TKIs. Conclusion: Plasma ddPCR is a potentially reliable method for detecting MET amplification in advanced NSCLC patients. Combined plasma ddPCR and tissue NGS might be an alternative or complementary method to MET amplification detection.